Integrating ZooMS and taphonomy further highlights differential processing of animal and Neandertal carcasses in the Quina Mousterian at Les Pradelles (Marillac‐le‐Franc, southwest France) - Pauline Raymond; Jean‐Jacques Hublin; Karen Ruebens; Geoff M. Smith; Sandrine Costamagno; Cédric Beauval; Alan Mann; Bruno Maureille (Journal of Quaternary Science, 2026)
The cave of Les Pradelles (Marillac‐le‐Franc, France) was repeatedly visited by Neandertals ~55 000 years ago and is a key site in discussions of Neandertal cannibalism. Excavations between 1967 and 1980 (Vandermeersch) and between 2001 and 2013 (Maureille/Mann) produced a rich faunal assemblage (>20 000 bones), alongside Quina Mousterian tools. Here, we provide a combined study of both collections integrating ZooMS (Zooarchaeology by Mass Spectrometry) and taphonomic analyses on morphologically unidentifiable bones (Vandermeersch [ n = 762] and Maureille/Mann [ n = 377]). Our results indicate excellent collagen preservation (99.2% identification rate) and consistent glutamine deamidation. While we note an increased representation of bovids and equids in the trabecular fraction, our results confirm Les Pradelles as a reindeer hunting camp. Differences in the fragmentation of Neandertal and reindeer carcasses are illustrated by the relatively low number of ZooMS‐identified Neandertal bones ( n = 5). We show that Neandertal processing was marginal compared to reindeer, but human bodies were processed on multiple occasions across the Quina Mousterian lithofacies. Abundant retouchers ( n = 23) and anthropogenic bone surface modifications (25%) were observed on the ZooMS‐identified fauna, but not on the newly identified Neandertal remains. We show the value of integrating ZooMS, taphonomic and zooarchaeological data to revisit curated collections.

Substantiating chemical groups for read-across using molecular response profiles - Rosemary E. Barnett; Thomas N. Lawson; Claudia Rivetti; Carlos Barata; Mark T.D. Cronin; Silvia Lacorte; Gavin R. Lloyd; Ralf J.M. Weber; Matthew J. Smith; Andrew D. Southam; Adam Biales; Kara Koehrn; et al. (Regulatory Toxicology and Pharmacology, 2025)

Identifying the unidentified fauna enhances insights into hominin subsistence strategies during the Middle to Upper Palaeolithic transition - Virginie Sinet-Mathiot; William Rendu; Teresa E. Steele; Rosen Spasov; Stéphane Madelaine; Sylvain Renou; Marie-Cécile Soulier; Naomi L. Martisius; Vera Aldeias; Elena Endarova; Paul Goldberg; Shannon J. P. McPherron; et al. (Archaeological and Anthropological Sciences, 2023)
Understanding Palaeolithic hominin subsistence strategies requires the comprehensive taxonomic identification of faunal remains. The high fragmentation of Late Pleistocene faunal assemblages often prevents proper taxonomic identification based on bone morphology. It has been assumed that the morphologically unidentifiable component of the faunal assemblage would reflect the taxonomic abundances of the morphologically identified portion. In this study, we analyse three faunal datasets covering the Middle to Upper Palaeolithic transition (MUPT) at Bacho Kiro Cave (Bulgaria) and Les Cottés and La Ferrassie (France) with the application of collagen type I peptide mass fingerprinting (ZooMS). Our results emphasise that the fragmented component of Palaeolithic bone assemblages can differ significantly from the morphologically identifiable component. We obtain contrasting identification rates between taxa resulting in an overrepresentation of morphologically identified reindeer ( Rangifer tarandus ) and an underrepresentation of aurochs/bison ( Bos/Bison) and horse/European ass ( Equus ) at Les Cottés and La Ferrassie. Together with an increase in the relative diversity of the faunal composition, these results have implications for the interpretation of subsistence strategies during a period of possible interaction between Neanderthals and Homo sapiens in Europe. Furthermore, shifts in faunal community composition and in carnivore activity suggest a change in the interaction between humans and carnivores across the MUPT and indicate a possible difference in site use between Neanderthals and Homo sapiens . The combined use of traditional and biomolecular methods allows (zoo)archaeologists to tackle some of the methodological limits commonly faced during the morphological assessment of Palaeolithic bone assemblages.

Monitoring holopelagic Sargassum spp. along the Mexican Caribbean coast: understanding and addressing user requirements for satellite remote sensing - Betsabé de la Barreda-Bautista; Sarah E. Metcalfe; Geoff Smith; Sofie Sjögersten; Doreen S. Boyd; Sergio Cerdeira-Estrada; Pablo López-Ramírez; Adolfo Magaldi; Rainer Ressl; Susana Perera-Valderrama; Hansel Caballero-Aragón; Oscar S. Siordia; et al. (Frontiers in Marine Science, 2023)
Massive influxes of holopelagic Sargassum spp. ( Sargassum natans and S. fluitans ) have been causing major economic, environmental and ecological problems along the Caribbean coast of Mexico. Predicting the arrival of the sargassum as an aid to addressing these problems is a priority for the government, coastal communities and the society; both mitigating the impacts and providing opportunities for its use. Lack of data concerning precise locations and times of sargassum beachings means that public and private funds are being spent inefficiently and most actions are reactive. The dynamic nature of sargassum beachings/influxes render conventional ground-based monitoring insufficient. Earth observation and cloud-based processing services offer tools to track, quantify and understand sargassum beaching remotely in a frequent, systematic and reliable manner with the temporal and spatial resolutions required for its management. In order to find the right solutions to address this problem, in this paper the needs and requirements of stakeholders are taken into consideration for the development of an Earth observation-based service to monitor sargassum along the Mexican Caribbean coast. Routine monitoring of sargassum over a large area will be cost effective and help mitigate the negative effects of sargassum influxes. The combination of imagery from Planet, specifically their SuperDove systems that provide daily data at 3 m spatial resolutions, with the freely available EU Copernicus data would be useful for many different stakeholders and potential users. A prototype of the service is presented, based on the main user requirements. The system would enable public and private organizations to allocate resources appropriately in affected areas quickly and efficiently, thereby minimizing economic, social and environmental impacts and enhancing the resilience of local communities. It would also assist the sargassum industry in the collection of fresh algae for onward processing. The system could easily be implemented for similar types of environmental monitoring in the Greater Caribbean and beyond.

Neanderthal subsistence, taphonomy and chronology at Salzgitter‐Lebenstedt (Germany): a multifaceted analysis of morphologically unidentifiable bone - Karen Ruebens; Geoff M. Smith; Helen Fewlass; Virginie Sinet‐Mathiot; Jean‐Jacques Hublin; Frido Welker (Journal of Quaternary Science, 2023)
Pleistocene faunal assemblages are often highly fragmented, hindering taxonomic identifications and interpretive potentials. In this paper, we apply four different methodologies to morphologically unidentifiable bone fragments from the Neanderthal open‐air site of Salzgitter‐Lebenstedt (Germany). First, we recorded zooarchaeological attributes for all 1362 unidentifiable bones recovered in 1977. Second, we applied zooarchaeology by mass spectrometry (ZooMS) to 761 fragments, and calculated glutamine deamidation values. Third, we assessed the collagen preservation of 30 fragments by near‐infrared spectroscopy (NIR) and, finally, we pretreated 10 bones with high predicted collagen values for radiocarbon dating. All returned dates at, or beyond, the limit of radiocarbon dating, indicating an age of older than 51 000 years ago. The ZooMS faunal spectrum confirms a cold environment, dominated by reindeer, alongside mammoth, horse and bison. The low occurrence of carnivore modifications (1%) contrasts with an abundance of human modifications (23%). Cut marks and marrow fractures were observed across reindeer, horse and bison. The mammoth remains are less well preserved and show a lower degree of human modifications, indicating, perhaps, a different taphonomic history. Overall, this study illustrates the importance of retaining, studying and incorporating the unidentifiable bone fraction to optimize interpretations of site formation and subsistence behaviour at Palaeolithic sites.

Agricultural systems regulate plant and insect diversity and induce ecosystem novelty - Jessie Woodbridge; Ralph Fyfe; David Smith; Anne de Varielles; Ruth Pelling; Michael J. Grant; Robert Batchelor; Robert Scaife; James Greig; Petra Dark; Denise Druce; Geoff Garbett; et al. (Anthropocene, 2023)

Prospects and problems: considerations for smallholder cattle grazing in oil palm plantations in South Kalimantan, Indonesia - Jori A. Bremer; Lisa A. Lobry de Bruyn; R. Geoff B. Smith; Wahyu Darsono; Tjeppy D. Soedjana; Frances C. Cowley (Agroforestry Systems, 2022)
Current Indonesian beef production only meets 45% of local demand. Increasing local beef production through integration of cattle production in pre-existing oil palm plantations is a possible solution to meeting this shortfall. The oil palm understorey provides feed, alleviating the need to convert additional land to agriculture. Smallholders are important contributors to both Indonesian cattle and palm oil production. This case study research seeks to understand key aspects of smallholder cattle management in palm oil production areas, to highlight opportunities and barriers to cattle integration. Thirty-nine smallholder cattle farmers from four villages in South Kalimantan were individually interviewed. The lack of alternative feed sources was the major driver towards the adoption of cattle production using oil palm understorey as feed. Cattle grazing was uncontrolled due to labour shortages and occurred in individually owned and ‘plasma’ plantations, with cattle penned at night where possible to avoid theft. Arrangements on land access and use between stakeholders are needed for systematic cattle grazing and to control cattle theft.

Combining collagen extraction with mineral Zn isotope analyses from a single sample for robust palaeoecological investigations - Jeremy McCormack; Nicolas Bourgon; Virginie Sinet-Mathiot; Zeljko Rezek; Geoff M. Smith; Jean-Jacques Hublin; Mohammed Dabain; Helen Fewlass (Archaeological and Anthropological Sciences, 2022)
Collagen extraction from bones or dentine, commonly used for radiocarbon ( 14 C) dating and stable carbon and nitrogen isotope (δ 13 C and δ 15 N) analyses, involves the dissolution of the bioapatite of skeletal elements. This fraction is typically disposed of during pretreatment. Here, we test the possibility of utilising this dissolved mineral solution for analysis of the bioapatite zinc isotope composition (δ 66 Zn). Bioapatite δ 66 Zn is a novel trophic level indicator similar to collagen δ 15 N but with isotopic fractionation independent from nitrogen, thus providing additional dietary information. We tested ways to minimise Zn contamination of the dissolved mineral phase during collagen extraction. We then used archaeological bone samples from Ain Difla (Jordan) and Ranis (Germany) to compare δ 66 Zn values of dissolved bioapatite following our collagen extraction protocol with δ 66 Zn values from the same sample material dissolved in a metal-free cleanroom. Our results demonstrate that with only minor adjustments to minimise Zn contamination, the dissolved mineral solution from collagen extraction protocols commonly employed for 14 C dating and (palaeo)dietary analysis can be used for additional δ 66 Zn analyses even when collagen extraction does not take place in a cleanroom. Our protocol allows us to gain an additional dietary proxy to complement δ 15 N trophic level interpretations and perform more robust (palaeo)ecological investigations without further destructive sampling.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Reflections on the scientific life and legacy of Professor Ted Milton (10 April 1954 – 8 June 2021) - Karen Anderson; Paul Aplin; Paul Curran; Jadunandan Dash; Angela Harris; Liz Rollin; John Shears; Geoff Smith; Robin Wilson (International Journal of Remote Sensing, 2021)

The impact of climate change and variability on coffee production: a systematic review - Yen Pham; Kathryn Reardon-Smith; Shahbaz Mushtaq; Geoff Cockfield (Climatic Change, 2019)

Effect of Arginine on the Aggregation of Protein in Freeze-Dried Formulations Containing Sugars and Polyol: II. BSA Reconstitution and Aggregation - Ellen Hackl; Joseph Darkwah; Geoff Smith; Irina Ermolina (AAPS PharmSciTech, 2018)

Effect of Arginine on the Aggregation of Protein in Freeze-Dried Formulations Containing Sugars and Polyol: 1—Formulation Development - Ellen Hackl; Joseph Darkwah; Geoff Smith; Irina Ermolina (AAPS PharmSciTech, 2018)

Micro-Structural Analysis of Tablet Surface Layers by Intelligent Laser Speckle Classification (ILSC) Technique: an Application in the Study of both Surface Defects and Subsurface Granule Structures - Ahmet Orun; Geoff Smith (Journal of Pharmaceutical Innovation, 2017)

A comparison of psychotic symptoms in subjects with methamphetamine versus cocaine dependence - Peter D Alexander; Kristina M Gicas; Taylor S Willi; Clara N Kim; Veronika Boyeva; Ric M Procyshyn; Geoff N. Smith; Allen E Thornton; William J Panenka; Andrea A. Jones; Fidel Vila-Rodriguez; Donna J. Lang; et al. (Psychopharmacology, 2017)

Process Understanding in Freeze-Drying Cycle Development: Applications for Through-Vial Impedance Spectroscopy (TVIS) in Mini-pilot Studies - Geoff Smith; Muhammad Sohail Arshad; Eugene Polygalov; Irina Ermolina; Timothy R McCoy; Paul Matejtschuk (Journal of Pharmaceutical Innovation, 2017)

Effect of Initial Spacing on First Thinning Product Recovery, and Financial Outcomes in Whitewood (Endospermum medullosum) Plantations in Vanuatu - R. Geoff B. Smith; Kevin Glencross; J. Doland Nichols; Graeme Palmer; Rexon Viranamangga (Small-scale Forestry, 2016)

The Whitewood (Endospermum Medullosum) Value-Chain in Vanuatu and Impediments to Development of a Plantation-Based Industry - Rexon Virannamanga; Kevin Glencross; Graeme Palmer; J. Doland Nichols; R. Geoff B. Smith (Small-scale Forestry, 2015)

Effect of acidic and basic pH on Thioflavin T absorbance and fluorescence - Ellen V. Hackl; Joseph Darkwah; Geoff Smith; Irina Ermolina (European Biophysics Journal, 2015)

Factors Affecting the Use of Impedance Spectroscopy in the Characterisation of the Freezing Stage of the Lyophilisation Process: the Impact of Liquid Fill Height in Relation to Electrode Geometry - Geoff Smith; Muhammad Sohail Arshad; Eugene Polygalov; Irina Ermolina (AAPS PharmSciTech, 2014)

Crown structure and vertical foliage distribution in 4-year-old plantation-grown Eucalyptus pilularis and Eucalyptus cloeziana - Philip J. Alcorn; David I. Forrester; R. Geoff B. Smith; Dane S. Thomas; Ryde N. James; Adrienne B. Nicotra; Jürgen Bauhus (Trees, 2013)

Adapting to climate change through local municipal planning: barriers and challenges - Thomas G. Measham; Benjamin L. Preston; Timothy F. Smith; Cassandra Brooke; Russell Gorddard; Geoff Withycombe; Craig Morrison (Mitigation and Adaptation Strategies for Global Change, 2011)

Retrieval of Substrate Bearing Strength from Hyperspectral Imagery during the Virginia Coast Reserve (VCR’07) Multi-Sensor Campaign - Charles M. Bachmann; C. Reid Nichols; Marcos J. Montes; Rong-Rong Li; Patrick Woodward; Robert A. Fusina; Wei Chen; Vimal Mishra; Wonkook Kim; James Monty; Kevin Mcilhany; Ken Kessler; et al. (Marine Geodesy, 2010)

Identification, Synthesis and Field Testing of (3Z,6Z,9Z)-3,6,9-Henicosatriene, a Second Bioactive Component of the Sex Pheromone of the Autumn Gum Moth, Mnesampela privata - Paul W. Walker; Geoff R. Allen; Noel W. Davies; Jason A. Smith; Peter P. Molesworth; Anna Nilsson; Fredrik Andersson; Erik Hedenström (Journal of Chemical Ecology, 2009)

Estimating spatial and temporal patterns of urban anthropogenic heat fluxes for UK cities: the case of Manchester - Claire Smith; Sarah Lindley; Geoff Levermore (Theoretical and Applied Climatology, 2009)

Effect of stocking on juvenile wood stiffness for three Eucalyptus species - Edward Warren; R. Geoff B. Smith; Luis Alejandro Apiolaza; John C. F. Walker (New Forests, 2009)

Physical map of two tammar wallaby chromosomes: A strategy for mapping in non-model mammals - Janine E. Deakin; Edda Koina; Paul D. Waters; Ruth Doherty; Vidushi S. Patel; Margaret L. Delbridge; Bianca Dobson; James Fong; Yanqiu Hu; Cecilia van den Hurk; Andrew J. Pask; Geoff Shaw; et al. (Chromosome Research, 2008)

The Ups and Downs of Life on the Edge: The Influence of Water Level Fluctuations on Biomass Allocation in two Contrasting Aquatic Plants - R. Geoff. B. Smith; Margaret A. Brock (Plant Ecology, 2006)

Dynamics of Tree Diversity in Undisturbed and Logged Subtropical Rainforest in Australia - R. Geoff B. Smith; J. Doland Nichols; Jerome K. Vanclay (Biodiversity and Conservation, 2005)

Some possible codes for encrypting data in DNA - Geoff C. Smith; Ceridwyn C. Fiddes; Jonathan P. Hawkins; Jonathan P.L. Cox (Biotechnology Letters, 2003)

Development of a Remote Electrode System for Monitoring the Water Content of Materials Inside a Glass Vial - Phe Man Suherman; Peter M. Taylor; Geoff Smith (Pharmaceutical Research, 2002)

Estimating the Economic Costs of Hydrologic Data Collection - Todd Goninon; Paul Pretto; Geoff Smith; Alan Atkins (Water Resources Management, 1997)